Global Health Education: a cross-sectional study among German medical students to identify needs, deficits and potential benefits (Part 2 of 2: Knowledge gaps and potential benefits) - Bozorgmehr, Kayvan (BioMed Central, 2010)
BACKGROUND: In Germany, educational deficits or potential benefits involved in global health education have not been analysed till now. OBJECTIVE: We assess the importance medical students place on learning about social determinants of health (SDH) and assess their knowledge of global health topics in relation to (i) mobility patterns, their education in (ii) tropical medicine or (iii) global health. METHODS: Cross-sectional study among medical students from all 36 medical schools in Germany using a web-based, semi-structured questionnaire. Participants were recruited via mailing-lists of students' unions, all medical students registered in 2007 were eligible to participate in the study. We captured international mobility patterns, exposure to global health learning opportunities and attitudes to learning about SDH. Both an objective and subjective knowledge assessment were performed. RESULTS: 1126 online-replies were received and analysed. International health electives in developing countries correlated significantly with a higher importance placed on all provided SDH (p ≤ 0.006). Participation in tropical medicine (p < 0.03) and global health courses (p < 0.02) were significantly associated with a higher rating of 'culture, language and religion' and the 'economic system'. Global health trainings correlated with significantly higher ratings of the 'educational system' (p = 0.007) and the 'health system structure' (p = 0.007), while the item 'politics' was marginally significant (p = 0.053). In the knowledge assessment students achieved an average score of 3.6 (SD 1.5; Mdn 4.0), 75% achieved a score of 4.0 or less (Q(25 )= 3.0; Q(75 )= 4.0) from a maximum achievable score of 8.0. A better performance was associated with international health electives (p = 0.032), participation in tropical medicine (p = 0.038) and global health (p = 0.258) courses. CONCLUSION: The importance medical students in our sample placed on learning about SDH strongly interacts with students' mobility, and participation in tropical medicine and global health courses. The knowledge assessment revealed deficits and outlined needs to further analyse education gaps in global health. Developing concerted educational interventions aimed at fostering students' engagement with SDH could make full use of synergy effects inherent in student mobility, tropical medicine and global health education.